Viabilidade Técnica/econômica no aproveitamento de água de chuva para fins não potáveis em uma instituição de ensino do amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The follow study aims to evaluate the potential of saving and exploit rainwater as alternative sources of water in three standard buildings of a Higher Education Institution located in the State of Amazonas. In this sense, the goal of this research is to characterize rainwater capture and utilization systems for non-potable use in urban areas. The study seeks to synthesize and contextualize some technical and economic aspects of the system, portraying a problem of water consumption in the world and in the country, to questions of use and savings generated. In order to illustrate and corroborate the research, an experimental study carried out on three models of buildings developed at the Federal University of Amazonas. Based on a survey of rainfall data from the region, in addition to other information obtained through consumption proportions of potable water replaceable by rainwater, an investigation was carried out on the potential of captation and economy before and after implementation of the rainwater harvesting system. Regarding quantitative aspects, the investigation was based on the comparison between the volumes captured by each one of the structures, in order to define the potential of reduction of the volume of water that is destined to the use in the discharges of sanitary ware, in laundry, water tanks, irrigation of gardens and car washes. The results indicate that the rainwater usage resulted in a reduction of expenses with potable water, as well being a viable alternative in terms of environmental gains for future generations. Therefore, it was proven that the implementation of a rainwater utilization system in the three standard buildings of the tested institution proves to be economically viable, indicating a reasonably short return of the investment and a remarkable potential of saving potable water.
Keywords: Sustentabilidade; Água pluvial - Aproveitamento; Viabilidade econômica; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO